Isolated Severe Right Ventricle Endomyocardial Fibrosis in a Child: Vanishing Tropical Disease Revisited. (November 2015) - Tripathi, Sushil P.; Phadke, Milind S.; Kerkar, Prafulla G.; Udare, Ashlesha S.
Abstract : Supplemental Digital Content is available in the text.